2015
DOI: 10.1161/hypertensionaha.114.04587
|View full text |Cite
|
Sign up to set email alerts
|

Aortic-Brachial Stiffness Mismatch and Mortality in Dialysis Population

Abstract: C ardiovascular disease is the leading cause of mortality in patients with chronic kidney disease. 1,2 Aortic stiffness, which results in increased pulse pressure (PP), cardiac overload, and left ventricular hypertrophy, is an established predictor for cardiovascular morbidity and mortality in chronic kidney disease. [3][4][5] Physiologically, the aorta is much more elastic than peripheral muscular arteries providing a physiological stiffness gradient. This physiological gradient of stiffness generates refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
130
3
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 35 publications
7
130
3
3
Order By: Relevance
“…In contrast, brachial (or femoral) ( Table 1) stiffness remains almost stable throughout aging ( Figure 1B, Table 2) and cannot negate for the effect of premature aortic aging on pressure transmission. 2,28, 29 Fortier et al 30 proposed arterial stiffness gradient as an independent index of ESRD survival. In our study, the predictive value of the arterial stiffness gradient depends entirely on aortic PWV changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, brachial (or femoral) ( Table 1) stiffness remains almost stable throughout aging ( Figure 1B, Table 2) and cannot negate for the effect of premature aortic aging on pressure transmission. 2,28, 29 Fortier et al 30 proposed arterial stiffness gradient as an independent index of ESRD survival. In our study, the predictive value of the arterial stiffness gradient depends entirely on aortic PWV changes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the predictive value of the arterial stiffness gradient depends entirely on aortic PWV changes. In the paper by Fortier et al, 30 the stiffness gradient was expressed as aortic PWV/brachial PWV and not in the usual way as (brachial PWV/aortic PWV) 0.5 . 2 The population in the work by Fortier et al 30 was older and included patients with diabetes, and the population was characterized principally by unusually low brachial PWV, which could account for the stiffness gradient as a better predictor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During aging, since the stiffness of the central elastic arteries increases to a greater extent than that of peripheral muscular arteries [2], the aortic/brachial stiffness gradient is first equalized (aortic stiffness = brachial artery stiffness), and then even reverted (aortic stiffness N brachial artery stiffness). This process, called aortic-brachial stiffness mismatch [3][4][5], has important hemodynamic and clinical consequences since it reduces the reflection waves, increasing the reflection site distance, causes vascular damage through the enhanced transmission of forward energy waves into the microcirculation [5], contributes to the pathogenesis of white matter lesions of the brain [6] and renal dysfunction [7,8] and, at least in patients with ESRD, is strongly and independently associated with increased mortality [9].inflammatory bowel disease (IBD) [10], we reported that aortic stiffness was increased [11] and that the aortic stiffening was reduced by antitumor necrosis factor (anti-TNF) therapy in young patients with IBD [12]. These findings were confirmed in several studies performed by independent groups, in meta-analyses performed by our group [13][14][15], and in a meta-analysis performed by an independent group that, methodologic issues aside [16], has also reported both increased intima-media thickness and reduced flow-mediated dilation in patients with IBD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both CKD and ulcerative colitis (UC) are characterized by an increase of aortic stiffness [1,9,[11][12][13][14][15]17]. However, since the causes and the mechanisms involved in the arterial stiffening seem to be different [10,20], also the arterial phenotype, the hemodynamic and the clinical consequences could be different in UC and CKD.…”
Section: Introductionmentioning
confidence: 99%